Kognisi Sosial Melalui Situs Jejaring Youtube Pada Komunitas Online (Studi Kasus pada Komunitas Online LinkPictureID) - Fitria Ayuningtyas; Ahmad Zakki Abdullah (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2017)
The Video portal known as Youtube has become one of the alternative broadcasting channels. As the Internet usage is increasing the use of visual form becomes a public space. A YouTuber, a popular slang for video producer on youtube has formed a style of its own, in which there are some interesting research studies, especially in the establishment of reality and social cognition. Videos that teached the perspective and expression of opinion is an example of how the youtuber shapes reality to the audience. This video was varied, ranging from animation, social experiment up to the high-level animation. Social cognition is becoming prominance, that the audience use video logic as a basis for understanding the various things in surrounding environment. However, the capacity and the youtuber background are very wide - range as they have no common standard to their profession as videographer. The aim of this study is an effort to observe how Youtube users see the social situation as a cognitive ability form the use of video. This study used theory about social cognition, social media and youtube. This study used qualitative method. The result of this study is an interaction between users and creators create a whole different kind of dialogue, given in this era of communication technology they are none other than Prosumen (producer-consumer). The rapid reproduction of this message is very dynamic, especially responding to social circumstances. This study focuses on an active online community focusing on the interaction CMC via youtube video portals as the establishment of social cognition.The conclusion this study was social cognition thru youtube give us new perspective that we can get creative as well as possible to be able to work freely. In this study, the community used youtube as reference and benchmark. In this case, LinkPicture ID community well understand about “upgrade” concept that required to speed up in taking a decision based on the dynamics that happened. Portal video Youtube telah menjadi salah satu saluran penyiaran alternatif. Penggunaan internet yang semakin meningkat membentuk sebuah ruang penggunaan visual yang bebas. Youtuber, sebutan untuk para produsen video di youtube telah membentuk sebuah nuansa tersendiri, didalamnya terdapat beberapa kajian kajian menarik terutama di pembentukan realita dan kognisi sosial. Video-video yang mengajarkan cara pandang dan pengungkapan opini maupun pendapat adalah contoh bagaimana para youtuber membentuk realita terhadap penontonnya. Kognisi sosial dalam pandangan ini sangatlah penting mengingat bahwa para penonton menggunakan logika video tersebut sebagai dasar dalam memahami berbagai hal disekitar lingkungannya. Namun demikian kapasitas maupun latar belakang para youtuber ini sangat bermacam–macam mengingat mereka tidak memiliki standard umum terhadap profesi mereka sebagai videografis. Tujuan penelitian ini untuk melihat bagaimana pengguna youtube melihat keadaan sosial sebagai kemampuan koginitif. Teori yang digunakan dalam penelitian ini yaitu kognisi sosial, situs jaringan sosial, dan youtube. Penelitian ini menggunakan metode penelitian kualitatif. Adapun hasil dari penelitian ini adalah interaksi antar pengguna dan pembuat video merupakan interaksi yang sangat berbeda, mengingat di era teknologi komunikasi ini mereka tidak lain dari produsen-konsumen. Pesatnya reproduksi pesan ini sangatlah dinamis terutama menanggapi keadaan sosial. Penelitian ini memfokuskan diri pada sebuah komunitas online yang aktif dan mengutamakan interaksi CMC lewat portal video youtube sebagai pembentukan kognisi sosial. Kesimpulan kognisi sosial melalui youtube memberikan pandangan bahwa kita bisa berkreasi sebaik mungkin untuk bisa berkarya secara bebas. Adapun penggunaan youtube sebagai sebagai referensi dan pembanding. Dalam hal ini, komunitas LinkPictureID paham dengan konsep “upgrade” dimana diperlukan sebuah kecepatan dalam mengambil keputusan berdasarkan dinamika yang terjadi.